2010
DOI: 10.1073/pnas.0905185107
|View full text |Cite
|
Sign up to set email alerts
|

Universal model for water costs of gas exchange by animals and plants

Abstract: For terrestrial animals and plants, a fundamental cost of living is water vapor lost to the atmosphere during exchange of metabolic gases. Here, by bringing together previously developed models for specific taxa, we integrate properties common to all terrestrial gas exchangers into a universal model of water loss. The model predicts that water loss scales to gas exchange with an exponent of 1 and that the amount of water lost per unit of gas exchanged depends on several factors: the surface temperature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 37 publications
(46 reference statements)
4
96
1
Order By: Relevance
“…1, Table 1) and a role for the increased haemolymph volume in active ventilation. Interestingly, this contradicts the suggestion that CO 2 accumulation during DGC results in longer spiracle opening than is necessary for oxygen uptake, and thus that exhibiting the pattern incurs a water vapour loss penalty (Woods and Smith, 2010). An additional effect of haemolymph water loss on oxygen supply could be that of elevated fluid viscosity, which would further limit what is already the main barrier for oxygen supply: namely, diffusion through the fluid-phase from the tracheole terminals to the tissues (Timmins et al, 2000).…”
Section: Discussioncontrasting
confidence: 51%
“…1, Table 1) and a role for the increased haemolymph volume in active ventilation. Interestingly, this contradicts the suggestion that CO 2 accumulation during DGC results in longer spiracle opening than is necessary for oxygen uptake, and thus that exhibiting the pattern incurs a water vapour loss penalty (Woods and Smith, 2010). An additional effect of haemolymph water loss on oxygen supply could be that of elevated fluid viscosity, which would further limit what is already the main barrier for oxygen supply: namely, diffusion through the fluid-phase from the tracheole terminals to the tissues (Timmins et al, 2000).…”
Section: Discussioncontrasting
confidence: 51%
“…A similar positive relationship was previously found in five ant species (Schilman et al, 2005) as well as in species from two families of beetles; this correlation was stronger in species from dry than mesic environments (Zachariassen et al, 1987). Moreover, Woods and Smith (Woods and Smith, 2010) proposed a universal model which predicts that WLR scales to gas exchange with an exponent of 1 based on the results of 202 different species including 30 species of insects. The increase in RWL with increasing metabolic rate supports the hypothesis that species adapted to xeric environments have a lower standard metabolic rate compared with species adapted to mesic ones [e.g.…”
Section: Rwlsupporting
confidence: 50%
“…The pattern of crossresistance in our previous study (Bubliy et al, 2012a) indirectly indicated that a reduced metabolism might be responsible for increased desiccation tolerance in D. melanogaster after hardening at low RH. It is known that terrestrial animals lose water in the process of respiration (Schmidt-Nielsen, 1997), and some recent findings demonstrate a strong correlation between the water loss rate and the rate of exchange for metabolic gases (Woods and Smith, 2010). However, the contribution of respiratory transpiration to overall water loss is not always evident in insect studies, including those performed on Drosophila (for reviews, see Chown, 2002;Chown and Nicolson, 2004).…”
Section: Stress-induced Plastic Responsesmentioning
confidence: 99%